Coordination of Patient Transfer Process and Role of the Center for Treatment Guidance and Information of Tabriz University of Medical Sciences - faramarz pourasghar; jafarsadegh tabrizi; nesa kavakebi; ahad banagozar mohammadi (Tehran University of Medical Sciences, 2015)
Background: Patient transfer requires the wide variety of functions such as collaboration, appropriate communication and coordination between hospitals and the Center for Treatment Guidance and Information (CTGI). This study aimed at determining the influencing factors in the coordination of patient transfer and also explaining the situation of the CTGI in patient transfer process coordination. Materials and Methods: This study was a qualitative study (phenomenology) conducted using three Focus Group Discussions (FGD) and thirty interviews with participants who were involved in the process of patient transfer in a referring hospital, six patient receiver hospitals and CTGI in Tabriz. Purposive sampling was used to select study participants. Data was analyzed using content analysis. Results: The effective factors of the patient transfer coordination were categorized in four main themes including weakness in the exchange of clinical information, data constraints, legal protections weakness and guidelines implementation and lack of clinical empowerment in managing patient. Eighteen sub-themes were identified which include legal protections weakness and guidelines implementation in center for treatment guidance as sector problems. Conclusion: There are some problems in coordination of patient transfer process which is relate to non adherence a specific procedure for admission , ineffective interactions and information exchange. In order to achieve uninterrupted medical treatment, the patient transfer coordination should be improved. The center for treatment guidance and information should be obtained its position as a supervising authority.